CRISPR-Mediated Knockout of Long 3′ UTR mRNA Isoforms in mESC-Derived Neurons - Bae, Bongmin; Miura, Pedro (Frontiers in Genetics, 2021)
Alternative cleavage and polyadenylation (APA) is pervasive, occurring for more than 70% of human and mouse genes. Distal poly(A) site selection to generate longer 3' UTR mRNA isoforms is prevalent in the nervous system, affecting thousands of genes. Here, we establish mouse embryonic stem cell (mESC)-derived neurons (mES-neurons) as a suitable system to study long 3' UTR isoforms. RNA-seq analysis revealed that mES-neurons show widespread 3' UTR lengthening that closely resembles APA patterns found in mouse cortex. mESCs are highly amenable to genetic manipulation. We present a method to eliminate long 3' UTR isoform expression using CRISPR/Cas9 editing. This approach can lead to clones with the desired deletion within several weeks. We demonstrate this strategy on the Mprip gene as a proof-of-principle. To confirm loss of long 3' UTR expression and the absence of cryptic poly(A) site usage stemming from the CRISPR deletion, we present a simple and cost-efficient targeted long-read RNA-sequencing strategy using the Oxford Nanopore Technologies platform. Using this method, we confirmed specific loss of the Mprip long 3' UTR isoform. CRISPR gene editing of mESCs thus serves as a highly relevant platform for studying the molecular and cellular functions of long 3' UTR mRNA isoforms.